Signal-noise support vector model of a microwave transistor - Gunes, Filiz; Turker, Nurhan; Gurgen, Fikret (WILEY, 2007)
In this work, a support vector machines (SVM) model for the small-signal and noise behaviors of a microwave transistor is presented and compared with its artificial neural network (ANN) model. Convex optimization and generalization properties of SVM are applied to the black-box modeling of a microwave transistor. It has been shown that SVM has a high potential of accurate and efficient device modeling. This is verified by giving a worked example as compared with ANN which is another commonly used modeling technique. It can be concluded that hereafter SVM modeling is a strongly competitive approach against ANN modeling.
Keywords: support vectors; artificial neural networks; generalization; global optimization; microwave transistor; scattering parameters; noise parameters; Computer Science; Engineering